OPTIMALISASI SISTEM GROUNDING PADA FASILITAS DPPU YIA: STUDI KASUS DAN REKOMENDASI PERBAIKAN - Amrullah, Rizky; Kuspranoto, Abdul Haris (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2024)
Activities The grounding system is an important component in electrical installations, especially in high-risk facilities such as Aircraft Filling Depots (DPPU). This study aims to evaluate the grounding system at DPPU Yogyakarta International Airport (YIA), including fuel tanks, pumps, generators and lightning rods, and provide recommendations to improve its reliability. Measurements were carried out using the straight line stretch method (0–5m–10m) according to PUIL 2000 and SNI 04-6918-2002 standards. The results show that most facilities have resistance below 5 ohms, such as tanks (0.74–0.88 ohms), LDP pumps (0.96–0.97 ohms), generators (0.97 ohms), and diesel pumps (1.16 ohms). The grounding system at this facility is considered adequate and safe for operations. However, the resistance of the lightning rod reached an average of 219 ohms, well above the standard limit. Pole damage due to corrosion and the possibility of broken grounding cables are the main causes of high resistance. This condition poses a high risk to safety and needs to be repaired immediately. The recommendations put forward include replacing lightning protection poles, reinstalling grounding cables, as well as additional protection for grounding cables at other facilities to prevent operational damage. Regular maintenance and periodic inspections are also recommended to maintain the performance of the grounding system in the long term. Most of the grounding systems at DPPU YIA meet national standards, immediate repairs to the lightning rods are necessary to improve the safety and reliability of the facility. These findings can be a reference for optimizing grounding systems in similar facilities.